Perturbed expression pattern of the immediate early gene Arc in the dentate gyrus of GluA1 C‐terminal palmitoylation‐deficient mice - Masayuki Itoh; Hiroyuki Okuno; Daisuke Yamada; Mariko Yamashita; Manabu Abe; Rie Natsume; Toshie Kaizuka; Kenji Sakimura; Mikio Hoshino; Masayoshi Mishina; Keiji Wada; Masayuki Sekiguchi; et al. (Wiley, 2019)
Abstract Background AMPA receptors predominantly mediate fast excitatory synaptic transmission in the mammalian brain. Post‐translational protein S‐palmitoylation of AMPA receptor GluA subunits at their C‐termini reversibly controls the receptors trafficking to and from excitatory glutamatergic synapses. Excitatory inputs to neurons induce the expression of immediate early genes (IEGs), including Arc, with particular spatial patterns. In the hippocampal dentate gyrus, Arc is mainly expressed in the upper (dorsal) blade at the basal state. GluA1 C‐terminal palmitoylation‐deficient (GluA1C811S) mice showed enhanced seizure susceptibility and disturbed synaptic plasticity without impaired gross anatomy or basal synaptic transmission. These mutant mice also exhibited an increased expression of IEG products, c‐Fos and Arc proteins, in the hippocampus and cerebral cortex. In this report, we further analyzed excitability and Arc expression pattern in the dentate gyrus of GluA1C811S mice. Methods and Results Electrophysiological analysis of granule neurons to measure the evoked excitatory postsynaptic current/evoked inhibitory postsynaptic current ratio revealed that excitatory/inhibitory (E/I) balance was normal in GluA1C811S mice. In contrast, immunohistochemical staining showed an abnormal distribution of Arc‐positive cells between upper and lower (ventral) blades of the dentate gyrus in these mutant mice. These data suggest that deficiency of GluA1 palmitoylation causes perturbed neuronal inputs from the entorhinal cortex to the dentate gyrus, which potentially underlies the excessive excitability in response to seizure‐inducing stimulation. Conclusion Our findings conclude that an appropriate regulation of Arc expression in the dentate gyrus, ensured by AMPA receptor palmitoylation, may be critical for stabilizing hippocampal neural circuits and may suppress excess excitation.